(untitled) (The Research of Medical Science Review, 2025)
Background Intraepithelial bullae, skin and mucous membrane erosions are hallmarks of the autoimmune disease pemphigus vulgaris. Assessing the clinical and demographic characteristics of individuals with pemphigus vulgaris (PV) who came to our department was our objective. Methods A cross-sectional study was conducted in the Dermatology Department of the Pakistan Emirates Military Hospital from December 2023 to June 2024. It included patients aged 18 to 70 with pemphigus vulgaris (PV) confirmed by histopathology and immunofluorescence. Fifty patients were categorised into mild, moderate, and severe PV based on severity scores. Results The study involved 50 patients with various histopathological types of pemphigus vulgaris. The mean age was 52.3 years (SD = 14.6), ranging from 18 to 70 years. The cohort included 23 females (46.0%) and 27 males (54.0%). A family history of pemphigus vulgaris was present in 22 patients (44.0%). Clinically, 39 patients (78.0%) had mucocutaneous pemphigus vulgaris (MCPV), 10 (20.0%) had mucosal pemphigus vulgaris (MPV), and 1 (2.0%) had skin-only involvement. At presentation, 94.0% reported oral esions, and 34.0% experienced dysphagia. The disease duration averaged 44.5 onths. Severity ranged from mild in 42.0% to severe in 22.0%, with 42.0% xperiencing a relapse. Conclusion Our region's pemphigus vulgaris (PV) patients' clinical and demographic findings were consistent with those of earlier research.